A Comparison of Ice Cold Water Pretreatment and α-Bromonaphthalene Cytogenetic Method for Identification of Papaver Species. (11th September 2013) - Rezaei Osalou, Amir; Daneshvar Rouyandezagh, Sheida; Alizadeh, Behrouz; Er, Celal; Sevimay, Cafer Sirri
Abstract : The plants belonging to many species in genus Papaver are very similar and have very small chromosomes that make identification very difficult. The study aimed to compare the effects of α -bromonaphtalene and ice cold water pretreatment to identify chromosomes of Papaver species collected from different areas of Iranian West Azerbaijan and Turkish Van, Agri and, Hakkari provinces. The seeds were germinated in Jacobson trays at 24°C under continuous light. Thereafter, roots from 1.5 cm long plantlets were pretreated with α bromonaphtalene for 15, 30, and 45 min or at 0°C in ice cold water for 24 h before fixing, hydrolyzation, and feulgen staining. The ice cold water pretreatment was more appropriate and easy to determine chromosomes. Seeds from seven samples did not germinate. Sixty samples out of the rest of 62 samples were identified as P. pseudo orientale, one sample was identified as P. bracteatum, and another as P. orientale . This is the first study that used ice cold water to determine the chromosomes in papaver species. It is hoped that it will also facilitate to determine chromosome number and identify other papver species.